2020
DOI: 10.7759/cureus.6892
|View full text |Cite
|
Sign up to set email alerts
|

Myomatous Erythrocytosis Syndrome: Case Report and Review of the Literature

Abstract: Myomatous Erythrocytosis Syndrome is defined as erythrocytosis, myomatous uterus, and the return of normal hematologic values following surgical resection. The exact role of erythropoietin in disease pathogenesis is unknown. In this study we report the case of a 49 year old premenopausal woman who was found to have an enlarged heterogeneous mass arising from the uterus concerning for malignancy. Her RBC count was 5.75 T/L, hemoglobin was 17.6 g/dL and hematocrit was 54.3%. Pre-operative erythropoietin levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Under rare conditions, secondary erythrocytosis can originate from benign tumors, such as uterine myoma[ 4 ], which is called myomatous erythrocytosis syndrome. As myoma may cause abnormal uterine bleeding, which leads to fluctuations in hemodynamics such as anemia, the actual occurrence of MES may be higher than reported[ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 92%
“…Under rare conditions, secondary erythrocytosis can originate from benign tumors, such as uterine myoma[ 4 ], which is called myomatous erythrocytosis syndrome. As myoma may cause abnormal uterine bleeding, which leads to fluctuations in hemodynamics such as anemia, the actual occurrence of MES may be higher than reported[ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 92%
“…Emerging evidence shows that EPO is produced ectopically in uterine fibroid tissue in addition to the renal cortex, which can produce EPO and promote RBC production. Recently, Suresh and Rizk [9] discovered positivity of EPO immunohistochemistry in fibroid tissue, and the authors detected an increase in EPO level in blood serum, which returned to normal levels after removal of the mass. Moreover, Shu et al [10] found that EPO immunohistochemical staining was strongly positive in the myoma tissue, which may be the cause of erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the presence of an arteriovenous shunt, intra-uterine myoma, and increasing deoxygenated blood flow may lead to an increase in the production of RBC [6]. However, this hypothesis was rejected because the arteriovenous fistula tends to affect the focal area rather than the whole hemodynamic system [3], and microscopic examination results of myoma in patients with or without MES were similar [9]. Another hypothesis is the compression theory, in which the diaphragm is compressed by a large myoma and leads to hypoxic conditions, or the renal parenchyma is affected by mass compression, which then causes an increase in EPO production [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation